State and peculiarities of students’ functional preparedness for physical loads at the stage of adaptation to the training process - Бондаренко [Sergiy Bondarenko], Сергій Васильович; Дарзинська [Nataliya Darzinska], Наталія Олександрівна; Сидило [Liudmila Sidilo], Людмила Василівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--> A problem of students’ adaptation to the academic workload has been considered based on the analysis of dynamics of indicators of the cardiovascular and cardiorespiratory systems in the process of physical activity. The necessity to improve pedagogic control over their functional state has been demonstrated. Certain advantages of the universal cardiorespiratory indicator in the rapid diagnostics of functional states at the physical training classes have been proved. Abnormal (prenosological) states of the cardiorespiratory system of 17–18 years old students have been identified under light and moderate physical load which have to be taken into consideration and adjusted in the course of the class. A pattern of students’ self-control over the state of the cardiorespiratory system during physical activity has been proposed. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->